ANALISIS PERBANDINGAN STU DAN BRINETS KAITANNYA DENGAN KINERJA KARYAWAN PADA PT. BANK RAKYAT INDONESIA (Persero) Tbk CABANG NARIPAN DI WILAYAH BANDUNG TENGAH - Marliana Budhiningtias Winanti; Fitriah Agustina (Jurnal Teknologi dan Informasi (JATI), 2011)
STU and BRINETS are information systems which used by PT. BRI Branch Naripan to assist the employees in carrying out of banking activities. The purpose of this study is to determine the impact of the STU and BRINETS to performance of employee of PT. BRI Branch Naripan.The method that was used is descriptive and verivicative with the quantitative and qualitative approaches. To know the implementation of STU and BRINETS it could be seen from the Flow Map, Context Diagram and Data Flow Diagrams. Data collection techniques using observation techniques, interviews and questionnaires. Quantitative analysis using statistical correlation analysis Person Product Moment, Regression test, coefficient of determination an test t. While the qualitative analysis has more emphasis into the meaning, the definition of a particular situation.The result of research has been conducted by the researchers are level categories of respondents to the quality of the STU otherwise good and the response of respondents regarding the performance STU of employees has categotized good, produced strong and significant correlation level in improving employees are amounting to 51,9%. In hypothesis testing using the t test, obtained HA have been accepted or STU has impact into the employee performance in PT. BRI Branch Naripan. While the result of research conducted by researchers are level categories of respondents stated the quality BRINETS is very good and the response from the respondents regarding the performance of BRINETS, the employees has categorized good, resulted the level of the correlation is strong enough and significant in improving employee performance with the resulting impact percentage of BRINETS to the performance of employees that is equal to 35,5%. In hypothesis testing using the t test, obtained HA was acceptable or BRINETS has impact to the employee performance in PT. BRI Branch Naripan.